Original paperTactile sensitivity on the hands skin in rheumatic patients - Kaluga, Elżbieta; Kostiukow, Anna; Samborski, Włodzimierz; Rostkowska, Elżbieta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction: Clinical symptoms of rheumatic diseases can cause changes in the level of skin tactile sensitivity. Aim : To determine the tactile threshold of the hands in female patients with rheumatic diseases. It also attempted to determine correlations between rheumatic patients’ tactile sensitivity and the degree of articular movement limitations, the Barthel Index (BI) and Edinburgh Handedness Inventory (EHI) results, the level of disability of the right hand and the left hand as well as age, education and eyesight. Material and methods: Ninety-nine female rheumatic patients aged 19–87 years took part in the study. The control group comprised 45 healthy women aged 23–80 years. The measurement of the tactile threshold was performed using the Touch-Test TM Sensory Evaluators (Semmes-Weinstein Monofilaments Test). The tactile threshold was measured at three sites on the hand: the little finger, the index finger and the metacarpus. Results The patients’ tactile sensitivity ranges were classified as normal, diminished light touch and diminished protective touch. The degree of their disability was correlated with tactile sensitivity. The patients’ tactile sensitivity worsens with age, but it is not correlated with the level of education. The lateralization was similar to that of the control group and was not correlated with tactile sensitivity. The worsening eyesight, independent of rheumatic disease, corresponds, however, with decreasing tactile sensitivity. Conclusions : The patients represented a group with a medium level of functional disability and lower tactile sensitivity.